HUBUNGAN ANTARA PENGENDALIAN TITIK KRITIS PENGOLAHAN TERHADAP KEBERADAAN BAKTERI E.coli PINDANG IKAN LAYANG DI DESA TASIKAGUNG KABUPATEN REMBANG - Sukma Dewi Novianti; Sulistyani Sulistyani; Yusniar Hanani Darundiati (Jurnal Kesehatan Masyarakat (Undip), 2017)
Fish as fishery product is one of the animal protein sources. Shade processing is the technique that aims to preserve fish, but it can cause bacterial contamination. Food Quality Assurance System is needed to be conducted in this study, which is controlling the critical point of processing. This research aims to find out the relation of processing critical control point toward the presence of E.coli bacteria in flying fish Pindang. This research used quasi-experimental research by Post Test Only Control Design. The population of this research is flying fish Pindang at Pemindangan place of CV. Rizki Ilahi. There are 30 flying fish Pindang which are divided into 5 treatment group and one control group and there are 5 repetitions. Data analysis in this study used univariate and bivariate with Kruskal-Wallis test with  = 0,05. The results of this study indicated that there are differences in the presence of E.coli bacteria from each intervention of controlling critical point of processing, which proved by p-value = 0.001.The best critical control point to eliminate E.coli bacteria of flying fish Pindang is not to flush the fish with cold water and combination of all treatments. While, economically, the best critical control point to eliminate E.coli bacteria of flying fish Pindang is not to flush the fish with cold water.